Beg your pardon? The effect of communication costs on audit quality. Issue 6 (10th November 2021) - Deng, Yingwen; Xie, Lu; Zhang, Min; Wu, Yaqian
Abstract : We examine how language-induced communication costs affect audit quality by utilising unique data of signing auditors' native dialects and audit adjustments in China during 2006–2011. The results show that greater language-induced communication costs lead to lower audit quality. We further find that the negative effect of communication costs on audit quality is mitigated by extended audit tenure. Our study introduces linguistics theory into auditing and is the first to investigate the empirical impact of language-related communication costs in the audit context.